THE EFFECT OF SAVE LONG STORAGE CHICKEN EGGS AS A RESULT OF SOAKING IN GUVA LEAF EXTRACT (Psidium guajava L.) - D.S., Jehemat,; Wirapartha, M.; Umiarti, A.T. (Jurnal Peternakan Tropika, 2024)
This research aims to determine the effect on the quality of purebred chicken eggs soaked in guava leaf extract. The design used was a Completely Randomized Design (CRD) with 5 treatments and 4 replications. Each replication consisted of 3 eggs so that 60 eggs were used. The treatments used are; P1: Isa Brown chicken eggs without soaking in 30% guava leaf solution and without storage (control), P2: Isa Brown chicken eggs soaked in 30% guava leaf solution and stored for 7 days, P3: Isa chicken eggs Brown which was soaked in 30% guava leaf solution and stored for 14 days, P4: Isa Brown chicken eggs soaked in 30% guava leaf solution and stored for 21 days and P5: Brown Isa chicken eggs soaked in leaf solution guava 30% and stored for 28 days. The variables observed included egg weight, egg yolk index, haugh units, pH and egg yolk color. The results of the research showed that the effect of soaking guava leaf solution for 24 hours with a concentration level of 30% on egg weight (P1- P3), haugh units (P1-P2) statistically showed results that were not significantly different (P>0.05). The research results show that storage time affects the quality of purebred chicken eggs. The quality of chicken eggs decreases every week. In the variables egg weight, egg yolk index, haught unit and egg yolk color (P<0.05). The egg pH variable increased every week (P<0.05). Based on the results of the research conducted, it can be concluded that the effect of long storage at room temperature on the quality of broiler chickens soaked in guava leaf extract (Psidium guajava L.) for 24 hours at a concentration of 30% maintains egg weight until the 14th day. The quality of eggs in the Haugh unit is still grade B until 21 days of storage (P4). Day 0 (P1) to day 28 (P5) was able to maintain pH. Meanwhile, the egg yolk index and egg yolk color experienced a decline in quality up to 28 days. This occurs because the quality of the eggs decreases over the storage period.